The contradictions of capital in the twenty-first century : the Piketty opportunity - Hudson, Pat, 1948-; Tribe, Keith (Agenda, 2016)
This volume of essays builds upon renewed interest in the long-run global development of wealth and inequality stimulated by the publication of Thomas Piketty's Capital in the Twenty-First Century.